Efficiency of newly formulated camptothecin with β-cyclodextrin-EDTA-Fe3O4 nanoparticle-conjugated nanocarriers as an anti-colon cancer (HT29) drug - Krishnan, Poorani; Rajan, Mariappan; Kumari, Sharmilah; Syed, Sakinah; Priya, Sivan Padma; Fatin Amira; Danjuma, Lawal; Mok, Pooi Ling; Fakurazi, Sharida; Arulselvan, Palanisamy; Higuchi, Akon; Arumugam, Ramitha; et al. (Nature Publishing Group, 2017)
Camptothecin (CPT) is an anti-cancer drug that effectively treats various cancers, including colon cancer. However, poor solubility and other drawbacks have restricted its chemotherapeutic potential. To overcome these restrictions, CPT was encapsulated in CEF (cyclodextrin-EDTA-FE3O4), a composite nanoparticle of magnetic iron oxide (Fe3O4), and β-cyclodextrin was cross-linked with ethylenediaminetetraacetic acid (EDTA). This formulation improved CPT's solubility and bioavailability for cancer cells. The use of magnetically responsive anti-cancer formulation is highly advantageous in cancer chemotherapy. The chemical characterisation of CPT-CEF was studied here. The ability of this nano-compound to induce apoptosis in HT29 colon cancer cells and A549 lung cancer cells was evaluated. The dose-dependent cytotoxicity of CPT-CEF was shown using MTT. Propidium iodide and Annexin V staining, mitochondrial membrane depolarisation (JC-1 dye), and caspase-3 activity were assayed to detect apoptosis in CPT-CEF-treated cancer cells. Cell cycle analysis also showed G1 phase arrest, which indicated possible synergistic effects of the nano-carrier. These study results show that CPT-CEF causes a dose-dependent cell viability reduction in HT29 and A549 cells and induces apoptosis in colon cancer cells via caspase-3 activation. These data strongly suggest that CPT could be used as a major nanocarrier for CPT to effectively treat colon cancer.